Cynomorium songaricum Rupr. flavonoids improve cyclophosphamide-induced reproductive function damage by regulating the testosterone synthesis pathway - Chen, Jiarong; Yang, Xiaoyue; He, Zhongmei; Chen, Weijia; Zhao, Yan; Li, Jianming; Zong, Ying; Du, Rui (Frontiers in Pharmacology, 2024)
The prevalence of male infertility has been increasing globally, necessitating the search for safe and nontoxic active compounds to alleviate reproductive dysfunction. Although the precise mechanism remains unknown, Cynomorium songaricum Rupr. (CS) extract has protective effects on the reproductive system. The effect of C. songaricum Rupr. flavonoids (CSF) on reproductive injury and testicular mesenchymal stem cell viability in male mice and TM3 cells was investigated. Furthermore, we explored the possible association between these effects and the testosterone (T) synthesis pathway. Mice were administered cyclophosphamide to induce reproductive damage, followed by CSF administration. Body mass and organ index were recorded. Pathological changes in T and the epididymis were observed using hematoxylin-eosin staining. ELISA measured the serum levels of T, luteinizing hormone (LH), gonadotropin-releasing hormone (GnRH), follicle-stimulating hormone (FSH), and estradiol (E2) in mice. Fructose and zinc ion levels in the seminal plasma were measured. TM3 cells were treated with Bisphenol A (BPA) and different concentrations of CSF, followed by proliferative evaluations using the CCK-8 assay and T and LH level assessments using ELISA. Furthermore, the expression of steroidogenic enzyme genes and proteins was investigated using western blotting, and RT-PCRCSF exhibited a notable reduction in reproductive damage and improved pathological changes in testicular and epididymal tissues. CSF group demonstrated substantially higher levels of seminal plasma fructose and zinc ions; markedly elevated serum levels of T, LH, GnRH, and FSH; and lower levels of E2 than those of the model group. Intracellular T content and secretion of T and LH increase with CSF while effectively mitigating BPA-induced damage to TM3 cells. CSF group exhibited substantially higher gene and protein expression of steroidogenic enzymes than those of the model group, both in vivo and in vitro. CSF ameliorates reproductive impairment by enhancing the expression of pivotal enzymes involved in synthesizing T. The results show that CSF ameliorates cyclophosphamide-induced reproductive impairment and bisphenol A-induced TM3 cell damage in mice by regulating sex hormone levels in the Hypothalamic-Pituitary-Gonadal Axis (HPG axis) and upregulating the expression of steroidogenic enzymes. Therefore, CS is a potential treatment for male reproductive impairment.